Studies on the fermentation of molasses by Clostridium acetobutylicum - Barber, Jennifer Mary (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1978)
The bacterium Clostridium acetobutylicum produces acetone and n [subscript] - butanol from molasses in an industrial fermentation system. Although the bacterium has been cultured in liquid media it does not grow well on agar plates and requires high concentrations of hydrogen. Pretreatment of agar plates with bovine catalase improves growth on agar media. The bacteria produce an area of clearing (halo) on Potato agar plates due to butyric acid (the precursor of n [subscript]-butanol) and ÃŸ -amylase production. This characteristic will be used as a plate screening assay for the selection of high solvent producing mutants. A laboratory scale fermentation system was developed and detailed studies including pH, turbidity and cell morphology changes, and the details of solvent production were undertaken. The fermentation was optimized for mutant selection. The production of normal solvent yields by isolated clones is required for the mutant selection programme. Studies revealed that sporulation of the clones increased their solvent yield although solvent yields were still lower than normal. Efficient sporulation is therefore a prerequisite for clone fermentation. The origin of the phage infection during the factory outbreak was determined and resistant clones obtained. The presence of a bacteriocin-like toxin causing decreases in turbidity was identified during the final fermentation stage. The strain sensitivity, optimum conditions for stability as well as the kinetics of inactivation and lethality have been investigated. Preliminary characterization and purification studies indicate the proteinaceous nature of the toxin.,KMBT_363
Keywords: Molasses; Clostridium acetobutylicum; Fermentation